Numerical and experimental investigations on the flow and noise characteristics in a centrifugal fan with step tongue volutes. (August 2020) - Wei, Yikun; Zhu, Lingling; Zhang, Wei; Wang, Zhengdao
This paper presents numerical and experimental investigations on the flow and noise characteristics in a forward multi-blade centrifugal fan with step tongue volutes. Numerical simulations are performed by large eddy simulation, and the experiments are conducted to test the effects of the cut-off arrangements on the noise characteristics of the fan. The objective of this work is to explore the effect of the double-stepped tongue and single-stepped tongue on the internal complex flow and the noise generation within the fan. The comparison of the results of numerical calculation demonstrates that the internal complex flow of centrifugal fan can be controlled by the stepped tongue, the flow loss in meridian plane for the double-stepped tongue (HLHL, L stands for low and H for high) model is obviously lower than that of the original model, the Q-criterion value of HLHL model is lower than that of the original model, and the noise of the HLHL model produces an obvious decrease of 1.90 dB compared to that of the reference model. The comparison of the test results further shows that the HLHL model produces a decrease about 1.97 dB compared to that of the reference model, which mainly indicates the double-stepped tongue HLHL model more effectively controls the tonal noise comparing to the single-stepped tongue (HL) model. Meanwhile, the stepped arrangements possess comparable performance characteristics to the reference model. The double-stepped tongue HLHL model makes a positive contribution to the pressure rise of the centrifugal fan.